PERGELARAN WAYANG KRUCIL: Marginalisasi Warisan Budaya Panji di Jawa Timur - Irawanto, Rudi (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Wayang Panji is one of the variants of wayang krucil in Java. Wayang Panji was born in the era of King Joyoboyo's reign in the 11th century, although its birth phase is still an intepretative one. Wayang Panji displays local stories, which are different from the shadow puppets that take the story idea from India. Birth of puppets Panji allegedly as a form of rejection of local communities against new understandings. Shadow puppets that in the previous era is considered as a product of adi luhung began to be sued for its existence.Panji puppet is assumed as a form of resistance of Javanese society to the increasingly dominant immigrant culture. The resistance was not born in the center of Javanese culture in Yogyakarta or Surakarta but was born in East Java. East Java region tried to redefine the wayang art with different packaging. Wayang does not tell the gods but describes the local wisdom. Panji culture is not merely as a form of indigenous cultural archipelago but also a sign of cultural resistance to Javanese culture oriented to Central Java. East Java people want to show their characters in a more down to earth format.